Epigenetics ELSI: Darker Than You Think?. Issue 10 (October 2016) - Joly, Yann; So, Derek; Saulnier, Katie; Dyke, Stephanie O.M.
Abstract : Emerging ethical, legal, and social implications (ELSI) scholarship in epigenetics has focused largely on hypothetical issues involving institutional racism, discrimination, and eugenics. To avoid an unwarranted backlash against this promising research field, we encourage a more balanced ELSI discussion conveying the full spectrum of issues faced by stakeholders.